Investigating knowledge and perceptions of egg sharing among healthcare professionals in the United Kingdom. (May 2019) - Bracewell-Milnes, Timothy; Rajendran, Sara; Saso, Srdjan; Jones, Benjamin; Platts, Sophie; Cato, Sarah; Thum, Meen-Yau
Abstract: Objective: This study aims to determine the healthcare professionals knowledge and opinions of egg sharing and does this potentially effect egg sharing numbers in the UK? Study design: 304 healthcare professionals undertook a large, in-depth survey about various topics related to egg sharing. This included ranking key benefits and issues related to egg sharing. Statistical analysis was performed using SPSS. Results: 63.1% of respondents had little or no knowledge of egg sharing, although the majority supported the scheme once a short description was provided. Although attitudes towards egg sharing were positive, there was more support for voluntary donation. The issues surrounding egg sharing of most concern were the psychological well-being of the egg sharer if her own treatment is unsuccessful and the concern that giving away half her eggs reduces IVF success rates. Only 16.5% of respondents had previously referred a patient for egg sharing, with the majority citing lack of knowledge for the reason they hadn't referred. Conclusions: Egg sharing allows women to receive free or subsidised IVF in exchange for donating half their oocytes collected to a recipient. Although egg sharing was intended to solve the current donor oocyte shortage, egg sharing numbers have fallen over recent years. Education of healthcare professionals about the egg sharing programme and the research that supports it could improve their perceptions of egg sharing, increasing referral rates and egg sharing numbers.